Sistem Penunjang Keputusan Penilaian Guru Terbaik Dengan Metode Multi-Attributive Border Approximation (MABAC) - Muhammad Daffa Saefudin; Anis Mirza (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Al-Ma'mun Education Center School, starting in 2007 has provided formal education services and continues to improve the 8 standard of Islamic education services, one of the Al-Ma'mun Education Center schools is the SMK AMEC. So far, the assessment of teachers at SMK AMEC has not been done manually by the Principal in the teaching process, both majoring in Nursing, Pharmacy and Multimedia. When viewed from the system that has been running at SMK AMEC, teacher evaluation has never been done. In such a system, it is difficult for the Principal to decide which teacher is the best. This study aims to design and build a web-based decision support system using the MABAC method at SMK AMEC. With this decision support system, it is expected to provide fast, accurate and accurate decision making and to facilitate decision makers in the decision making process, And can help decision makers minimize mistakes when choosing the best teacher.